Analisis Kekuatan Mekanik Pipa Air dari Bahan Komposit Serbuk Kulit Kerang - Zulfikar, Achmad Jusuf; Siahaan, M Yusuf R; Irwan, Ade; Nasution, Fadly A. Kurniawan; Ritonga, Din Aswan A. (Fakultas Teknik UMSU, 2022)
Shellfish is one of the sources of natural wealth that is quite abundant and easy to obtain in the province of Sumatera Utara. In this study, shellfish will be used as an alternative raw material for the manufacture of water pipes. This study aims to obtain the average strength of the material against the bending and compressive loads imposed on the outer surface of the water pipe, calculate the distribution of the test result data by the Probability Density Function (PDF) method, and calculate the contribution of clamshell powder to the bending and compressive strength of the water pipe with the Anova and Tukey methods. Specimens are molded in the form of 2